Endothelial miRNAs as Cellular Messengers in Cardiometabolic Diseases. (March 2017) - Njock, Makon-Sébastien; Fish, Jason E.
Abstract : Metabolic syndrome is a clustering of risk factors that increases susceptibility to serious cardiometabolic complications, including type 2 diabetes (T2D) and myocardial infarction. Understanding the underlying mechanisms will advance the development of diagnostic and therapeutic approaches. A prominent feature of cardiometabolic diseases is endothelial dysfunction. Endothelial cell (EC) homeostasis and response to pathological stimuli are controlled by gene regulatory networks in which miRNAs play a critical role. Recently, miRNAs have been implicated as cell–cell messengers that can influence cellular function. This review investigates the known and potential roles for miRNA-based cell–cell communication in the control of cardiovascular health and explores the value of identifying miRNA biomarkers and developing therapeutics that harness or antagonize miRNA-based communication. Trends: Endothelial dysfunction is a prominent feature of cardiometabolic diseases and contributes to the prothrombotic and proinflammatory state of the vasculature. Endothelial cells secrete miRNAs to communicate with other cells in the cardiovascular system. Endothelial cells can also take up miRNAs secreted by other cell types and this modulates endothelial cell biology. Circulating miRNAs can be utilized as biomarkers of cardiovascular and metabolic diseases and extracellular vesicles could potentially be harnessed for the delivery of therapeutics such as miRNAs, to control cardiometabolic diseases including metabolic syndrome, diabetes, and atherosclerosis.